The implementation of probity audit to prevent fraud in public procurement of goods and services for government agencies - Hartadi, Toni; Arifin, Johan (Fakultas Ekonomi Universitas Islam Indonesia, 2020)
The procurement activities to obtain goods and services for government agencies in Indonesia are susceptible to becoming a medium of various types of fraud. Probity audit is a novel approach in which real-time audit is implemented in the process of goods and services procurement to overcome ongoing fraud issues. This study aimed to evaluate the implementation of probity audit with reference to applicable regulations. This research was a descriptive qualitative study analyzed using the document analysis method. The object of the study was the Inspectorate of the National Public Procurement Agency (LKPP) as the Government Internal Supervisory Apparatus of LKPP. The study results showed that, first, the suitability of facilities and infrastructure to implement probity audit was fairly good; second, the implementation of probity audit was satisfactory and in accordance with the guidelines for probity audit; third, the issue during the implementation of probity audit included the absence of policy and Standard Operating Procedure (SOP) for the implementation of probity audit in LKPP. This research was also expected to become one of the relevant sources for future researchers and assist the government in implementing the probity audit policy in Indonesia.